Gambling-Related completed suicides: a scoping review. (2nd November 2022) - Andreeva, Mariya; Audette-Chapdelaine, Sophie; Brodeur, Magaly
Abstract: Gambling disorder is a behavioral addiction with various consequences for those who suffer from it, such as lower quality of life, financial difficulties, psychiatric comorbidities, and increased suicide risk. The objective of this scoping review is to describe the available literature regarding gambling activities and completed suicides and underline future avenues of research on this important subject. We conducted an electronic literature search at the end of July 2021 in the following databases: Academic search complete, CINAHL +, APA Psyc Articles, APA Psyc Extra, Psychology and Behavioral Sciences Collection, Psyc Info, SOC Index, and SCOPUS. The search yielded a total of 1108 articles, of which 613 remained after the removal of duplicates. Upon title and abstract review, 51 articles remained. After full-text reading, a total of 18 articles were included in this review. To be selected, articles had to meet the following criteria: be published in a peer-reviewed journal, be available in English or French, and discuss gambling-related suicides as the main subject. The available literature shows distinct risk factors among suicide decedents with a history of problem gambling and that this population presents an elevated suicide risk. Recognizing and understanding the increased suicide risk in patients with gambling disorder will allow primary care professionals to provide better-adapted care to this population. To better comprehend this phenomenon further studies are required, with larger samples, qualitative or mixed-method designs, and a focus on diverse populations.